Pengembangan Game Virtual Reality Bertema Permainan Petak Umpet - Aruno Bagaskoro; Amir Hasanudin Fauzi; Fat’hah Noor Prawita (Universitas Telkom, 2026)
The rapid advancement of digital technology has shifted children's and teenagers' preferences from traditional games to digital ones, reducing physical activity and social interaction. To address this issue, this final project presents the development of an educational Virtual Reality (VR)-based game that adapts the traditional game of hide-and-seek. The game aims to revive interest in local cultural and social values through an engaging and interactive digital approach. The game was developed using Unity and C# programming language, targeting VR devices such as Meta Quest 3. Core features include a singleplayer mode, health/life system, hints, power-ups, and a 3D environment that supports exploration. The development process involved literature studies, user needs analysis, game flow design, UI implementation, and functionality and usability testing. Testing results indicate that the game provides a fun, immersive, and educational experience, and serves as an effective alternative medium for traditional cultural preservation in the digital era.